Congress in IML Moskva in commemoration of Plechanovs 100th birthday. Stuc̆ebys̆kova addresses the congress (1956)
Congress in IML Moskva in commemoration of Plechanovs 100th birthday. Stuc̆ebys̆kova addresses the congress.